Management of Student Group Projects in an Online Environment: The Experiences of UoN NUBS MSc International Students with Online Group Assessments during the COVID-19 Pandemic - Obiri, Emmanuel O. (2021)
The COVID-19 pandemic. It was officially declared a global pandemic by the World Health Organisation (WHO) on the 11th of March 2020 as a result of the worldwide spread of the novel coronavirus: Severe Acute Respiratory Syndrome Coronavirus 2 or SARS-CoV-2. As up until the writing of this research paper in the summer of the year 2021, the effects of the disruptions caused by the pandemic continue to be felt all over the world, cutting across all aspects of political, economic, socio-cultural, technological and environmental life. Within the full scope of these disrupted aspects of life, these effects continue to be relevant for millions of Higher Education students all over the world, specifically due to the disruptions to the operations of Higher Education institutions worldwide. This dissertation seeks to highlight the University of Nottingham’s (UoN) Nottingham University Business School (NUBS) MSc international students’ voices on their perceptions and experiences of managing online student group projects and assessments over the past 2020/21 academic year. For this purpose, in-depth semi-structured interviews were chosen to investigate the perceptions and experiences of 10 participant students from the NUBS MSc Operations Management and Information Systems (OMIS) division. This dissertation explores the perceptions of these participant MSc students concerning their online group assessments, and emphasises their experiences with communication and leadership in the management of their online student groups.